2021
DOI: 10.1016/j.jpurol.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of testicular microlithiasis as an incidental finding for the risk of testicular malignancy in children and the adult population: A systematic review. On behalf of the EAU pediatric urology guidelines panel

Abstract: ConclusionTM is a common incidental finding that does not seem to be associated with testicular malignancy during childhood, but in the presence of risk factors is associated with testicular malignancy in the adult population. Routine monthly self-examination of the testes is recommended in children with contributing risk factors from puberty onwards. When TM is still present during transition to adulthood a more intensive follow-up could be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, consensus on monitoring strategies in these patients is lacking. A recent systematic review of the literature including the follow-up of 595 children [81] showed that only one child with testicular microlithiasis exhibited testicular neoplasia during puberty. This observation suggests that testicular microlithiasis in children may be a common incidental finding on US with no clear association with testicular malignancy.…”
Section: Monitoring Children With Risk Factors For Testicular Tumorsmentioning
confidence: 99%
“…However, consensus on monitoring strategies in these patients is lacking. A recent systematic review of the literature including the follow-up of 595 children [81] showed that only one child with testicular microlithiasis exhibited testicular neoplasia during puberty. This observation suggests that testicular microlithiasis in children may be a common incidental finding on US with no clear association with testicular malignancy.…”
Section: Monitoring Children With Risk Factors For Testicular Tumorsmentioning
confidence: 99%
“…TM is relevant in the presence of a testicular tumor since this finding is usually encountered inside or in the periphery of the tumor [7]. In the pediatric population, microlithiasis in a radiologic result does not seem to be associated with testicular malignancy; in the case of teenagers with microlithiasis and risk factors, a monthly self-examination is recommended [8][9][10].…”
Section: Introductionmentioning
confidence: 99%